2000
DOI: 10.1093/humupd/6.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and reproduction

Abstract: Leptin, the product of the ob gene, is a small peptide molecule synthesized by white adipocytes with an important role in the regulation of body fat and food intake. Leptin and leptin receptor mRNA were first detected in the brain and hypothalamus but now their ubiquitous presence has been demonstrated. Leptin receptor signal transduction involves the activation of signal transducer and activator of transcription (STAT)-3, a member of the transcription family of proteins. Leptin is regulated by hormones and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(103 citation statements)
references
References 116 publications
1
101
0
1
Order By: Relevance
“…Another study has shown a possible relationship with the implantation process by demonstrating an increase in leptin receptor levels in healthy non-pregnant women during the menstrual cycle reaching a peak near ovulation, then declining at menstruation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown a possible relationship with the implantation process by demonstrating an increase in leptin receptor levels in healthy non-pregnant women during the menstrual cycle reaching a peak near ovulation, then declining at menstruation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these molecules were identified in balloon-like structures connected to the apical surface of granulosa cells . Leptin is localised in human and mouse ovaries (Gonzalez et al, 2000) and in human follicular fluid (Welt et al, 2003) pointing the potential source of exogenous leptin and the site of entry. Studies show that mitochondria regularly migrate during oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of leptin receptor in mouse, bat (Zhao et al, 2004), rat (Smith and Waddell, 2002) and human (Castellucci et al, 2000) placenta seems to support the idea of leptin's importance at the later stages of trophoblast invasion as well as during foetal development. In addition to its expression in the developing embryo, leptin has also been detected in mouse uterine fluid (Kawamura et al, 2003) and found to be secreted by human endometrium (Gonzalez et al, 2000). In vitro studies on mice showed that leptin stimulates the secretion of b3-integrin and promotes cell adhesion to the extracellular matrix proteins (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations